The Effect of RMD Utilization on School Quality: Evidence from Public Vocational Schools in Bandar Lampung - Novriyanti, Ella; Handoko, Handoko; Sari, Siti Rahma; Rusdiani, Atik; Sowiyah, Sowiyah (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2025)
The quality of vocational education is closely related to the effectiveness of school management and data-based governance. This study examines the effect of RMD, a regional education data management system, on the quality of public vocational schools in Bandar Lampung City. An explanatory quantitative approach with a cross-sectional survey design was employed. Data were collected from 263 teachers selected through proportional random sampling across nine public vocational schools. A Likert-scale questionnaire was used to measure RMD utilization and school quality, and the data were analysed using prerequisite tests and simple linear regression. The results indicate that RMD utilization has a positive and statistically significant effect on education quality. The coefficient of determination shows that RMD explains 46.8% of the variance in school quality. These findings confirm that effective use of data management systems contributes substantially to planning, monitoring, and evaluation processes in vocational schools. Strengthening data utilization practices is therefore essential to support transparency, accountability, and continuous improvement in vocational education.